2005
DOI: 10.1124/dmd.105.005710
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contributions of the Five Major Human Cytochromes P450, 1a2, 2c9, 2c19, 2d6, and 3a4, to the Hepatic Metabolism of the Proteasome Inhibitor Bortezomib

Abstract: ABSTRACT:VELCADE (bortezomib, PS-341), reversibly inhibits the 20S proteasome and exhibits cytotoxic and antitumor activities. Pretreatment of cancer cells with bortezomib increases the chemosensitivity of these cells, suggesting that bortezomib may be used in combination chemotherapy. The relative contributions of the five major human cytochromes P450 (P450s), 1A2, 2C9, 2C19, 2D6, and 3A4 (the focus of the present study), to the metabolism of bortezomib are an important aspect of potential drug interactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(91 citation statements)
references
References 27 publications
3
86
0
Order By: Relevance
“…We therefore sought to define the pharmacokinetics of bortezomib when given in this regimen. Because anthracyclines are metabolized by an aldoketoreductase (34) and cytarabine by cytidine deaminase (35), their pharmacokinetics are unlikely to be altered by bortezomib (36), which is hepatically metabolized by cytochrome P450 enzymes (37,38). Therefore, the pharmacokinetic studies were limited to that of bortezomib.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore sought to define the pharmacokinetics of bortezomib when given in this regimen. Because anthracyclines are metabolized by an aldoketoreductase (34) and cytarabine by cytidine deaminase (35), their pharmacokinetics are unlikely to be altered by bortezomib (36), which is hepatically metabolized by cytochrome P450 enzymes (37,38). Therefore, the pharmacokinetic studies were limited to that of bortezomib.…”
Section: Resultsmentioning
confidence: 99%
“…The pharmacokinetics of bortezomib is not affected by the degree of renal impairment, and therefore dosing adjustments are not necessary for patients with renal insufficiency, including patients requiring dialysis (57). This is because the primary metabolic pathway of bortezomib, as shown in in vitro studies, is oxidative deboronation by hepatic cytochrome P450 enzymes (57)(58)(59), mainly CYP3A4, CYP2C19, and CYP1A2 (57,59,60). U.S. Food and Drug Administration (FDA) approval of the labeling regarding the use of bortezomib in patients with renal impairment was based on the findings of a U.S. National Cancer Institute-sponsored dose-escalating and pharmacologic study (61).…”
Section: Pharmacokinetics and Dosing Of Novel Agents In Patients Withmentioning
confidence: 99%
“…There was no significant effect of CYP2C19 genotype on the response to treatment. CYP3A4 is considered to be a major contributor to the metabolism of bortezomib (5). In the present study, six patients were found to carry mutations in the CYP3A4 gene.…”
Section: Discussionmentioning
confidence: 78%
“…A previous study identified the percentage of each isoform to be 69.8, 33.5, 23.4, 15.8 and 13.6%, respectively (5). CYP3A4 and CYP2C19 are considered to be the principal metabolic enzymes for the inactivation of bortezomib (5).…”
Section: Introductionmentioning
confidence: 99%